FACTORS RELATED TO THE OCCURRENCE OF CHRONIC ENERGY DEFICIENCY (CED) IN PREGNANT WOMEN WORK AREA HEALTH CENTER JAYA KRUENG BARONA DISTRICT OF ACEH - Renjani, Rizky Swastika; Misra, Misra (Universitas Ubudiyah Indonesia, 2017)
The incidence of premature birth and low birth weight due to maternal malnutrition (chronic energy malnutrition/ CED, which is characterized by upper arm circumference of less than 23.5 cm. the number of pregnant women in the region of Krueng Barona Jaya health centers in 2016 amounted to 347 people who suffered as much as CED 20 people. To determine the relationship of age, education, parity, spacing pregnancies and disease with the incidence of maternal hamil.penelitian CED analytic with case control design. Sampling using purposive sampling technique with a sample of 40 respondents (20 respondents as a control and 20 respondents as the case) the data collection was carried out in 24 - Juni 29, 2017 in pregnant women at health centers working area Krueng Barona Jaya, Aceh Besar. The data collected by using questionnaire, then performed the chi-square test with a confidence level of 95% and the limit of significance (Î± = 0.05). Age has a risk to the CED in pregnant women (p = 0.003) (OR = 13.5), educational risk to the occurrence of at CED in pregnant women (p = 0.001) (OR = 13.2), parity risk to the occurrence of CED in pregnant women (p = 0.024) (OR = 6.0), spacing pregnancies have against the SEZ in pregnant women and infectious diseases also have exposure to the CED in pregnant women (p = 0.000) (OR = 17.0) , Age, education, parity, birth spacing and the risk of infectious diseases provides an opportunity to CED in pregnant women in Puskesmas Krueng Barona Jaya, Aceh Besar Year 2017. Results of this study can be a benchmark for assessment of nutritional status of pregnant women, so expect future health workers able to detect early so as to minimize the incidence of CED in pregnant women.Keywords: age, education, parity, spacing pregnancies, chronic energy deficiency